Connecting Scholarship in the Open: A Scoping Review of Academic Researcher Personal Learning Support Structures - Keefer, Jeffrey M. (Proceedings of the International Conference on Networked Learning, 2016)
Social media and public engagement play an increasing role in how people across ages, disciplines, and interests communicate with each other and perform their own lives. While different audiences participate for a diverse of reasons, researchers increasingly explore how connections are made, remain, and shift, along with the whats and whys these occur, especially within personal learning networks or environments related to academic learning (Buchem, Attwell, & Torres, 2011; Dabbagh & Kitsantas, 2012; Kop, 2011; Rahimi, Berg, & Veen, 2014; Veletsianos, 2012). Social media commonly promotes public conversationality, with personal learning networks and connected communities utilized by developing researchers while engaging in their learning and inquiries. While researcher development is a growing speciality within higher education academic discourse (McAlpine & Amundsen, 2009; McAlpine, Horn, & Rath, 2011; Wisker et al., 2010; Wisker, Robinson, Trafford, Lilly, & Warnes, 2004), little is known about researcher support structures of those engaging in research in public. With social media and networking technologies constantly shifting how people use, learn from, and make meaning through them, a scoping study is a useful methodology to explore this topic. Scoping studies examine the range and nature of an area of research, help determine the value of undergoing a full systematic review, summarize findings of previous studies, and serve to identify gaps in the literature (Arksey & O'Malley, 2005; Paré, Trudel, Jaana, & Kitsiou, 2015). While there are numerous kinds of literature reviews, scoping studies are particularly useful when a rapid overview of the literature is needed to broadly map what is currently known about an area (Pham et al., 2014), especially one that is not directly linked to specific disciplinary communities or functions where an established coherent portion of literature exists. The question guiding this study is: How do developing researchers learn in networked public spaces? The findings of this research work in progress will be presented during the Pecha Kucha.